The role of aluminum, silicium and their oxides in the process of graphitizing inoculation of cast irons - E. L Marukovich; V. I. Stetsenko; A. G. Solovej (Литьë и металлургия, 2001)
It is shown silicium and alluminium play the main role in the graphitizing inoculation process, not their oxides.